Skin hyperpigmentation in Indian population: Insights and best practice - Stephanie Nouveau; Divya Agrawal; Malavika Kohli; Francoise Bernerd; Namita Misra; Chitra Shivanand Nayak (Wolters Kluwer Medknow Publications, 2016)
Skin pigmentation is one of the most strikingly variable phenotypes in humans, therefore making cutaneous pigmentation disorders frequent symptoms manifesting in a multitude of forms. The most common among them include lentigines, postinflammatory hyperpigmentation, dark eye circles, and melasma. Variability of skin tones throughout the world is well-documented, some skin tones being reported as more susceptible to pigmentation disorders than others, especially in Asia and India. Furthermore, exposure to ultraviolet radiation is known to trigger or exacerbate pigmentation disorders. Preventive strategies for photoprotection and treatment modalities including topical and other medical approaches have been adopted by dermatologists to mitigate these disorders. This review article outlines the current knowledge on pigmentation disorders including pathophysiology, molecular profiling, and therapeutic options with a special focus on the Indian population.